A strategic approach to improve sustainability in transportation service procurement - Jothi Basu, R.; Bai, Ruibin; Palaniappan, PL.K. (Elsevier, 2015)
This paper focuses on the procurement of full truck-load transportation service with the view to ensuring sustainability in transport logistics. The carrier assignment problem (CAP) involved in truck load contract auction is studied using a complete enumeration method and heuristic approach. Performance of both methods is compared in terms of solution quality and computational time based on the results of sample problems considered. Also, the impact of combinatorial bidding on reducing empty haul in real world case is analyzed and environmental sustainability is achieved through reduction in carbon foot print.